Predictors of Neurological and Functional Recovery in Patients with Moderate to Severe Ischemic Stroke: The EPICA Study - Manuel Murie-Fernández; Mercedes Molleda Marzo (Stroke Research and Treatment)
Background. Improving our knowledge about the impact of restorative therapies employed in the rehabilitation of a stroke patient may help guide practitioners in prescribing treatment regimen that may lead to better post-stroke recovery and quality of life. Aims. To evaluate the neurological and functional recovery for 3 months after an acute ischemic stroke occurred within previous 3 months. To determine predictors of recovery. Design. Prospective observational registry. Population. Patients having suffered acute moderate to severe ischemic stroke of moderate to severe intensity within the previous 3 months with National Institutes of Health Stroke Scale (NIHSS) score from 10 to 20, 24 hours after arrival at emergency room (ER). Methods. All prespecified variables (sociodemographic and clinical data, lifestyle recommendations, rehabilitation prescription, and neurological assessments) were assessed at three visits, i.e., baseline (D0), one month (M1), and three months (M3). Results. Out of 143 recruited patients, 131 could be analysed at study entry within 3 months after stroke onset with a mean acute NIHSS score of 14.05, decreased to 10.8 at study baseline. Study sample was aged 64.9±13.8 years, with 49.2% of women. Neurorehabilitation treatment was applied to 9 of 10 patients from the acute phase and for three months with different intensities depending on the centre. A large proportion of patients recovered from severe dependency on activities of daily living (ADL) at D0 to a mild or moderate disability requiring some help at M3: mean NIHSS=10.8 to 5.7; median modified Rankin Scale mRS=4 to 3; Barthel index BI=40 to 70; all p values<0.001. Multivariate analyses integrating other regression variables showed a trend in favour of rehabilitation and revascularization therapies on recovery although did not reach statistical significance and that the positive predictors of recovery improvement were baseline BI score, time to treatment, and dietary supplement MLC901 (NurAiD™II). A larger percentage of patients with more severe stroke (NIHSS>14) who received MLC901 showed above median improvements on mRS compared to control group at M1 (71.4% vs. 29.4%; p=0.032) and M3 (85.7% vs. 50%; p=0.058). Older subjects and women tend to have less improvement by M3. Conclusions. Our study in patients with moderate to severe stroke shows overall recovery on neurological and functional assessments during the 3 months of study observation. Apart from demonstrating traditional “non-modifiable” predictors of outcome after stroke, like age, sex, and stroke severity, we also detected association between the use of dietary supplement MLC901 and recovery.